Nutritive and sensory quality of commercial dry - fermented sausages - ”ČAJNA” type with different salt content - Odžaković, Božana; Grujić, Slavica; Ivanović, Dragana; Vučić, Goran (Journal of Engineering & Processing Management, 2021)
The aim of this study was to evaluate the quality of dry-fermented pork sausages – “čajna” type from the market, with similar composition and different salt content. Physicochemical parameters of selected samples were determined and sensory quality parameters were evaluated. In samples M and D, with significantly higher (P ≤ 0.05) sodium chloride content, higher values of color parameter a* and breaking force and lower values of pH and water activity were found compared to samples T and L. Sample D had the highest protein (25.51%) and sodium chloride content (5.04%), and the lowest fat content (30.04%). Samples M and D had significantly higher sensory quality, especially odor, aroma, taste, consistency and cross-section, compared to other samples. These samples were evaluated as sausages with a pronounced pleasant aroma, taste and odor characteristic for dry-fermented products, with pleasant salinity, appropriate for the product. Although the dry-fermented sausage samples with a lower salt content had more acceptable nutritive values, their sensory quality was lower than expected.